Are thyroid nodules associated with sex-related hormones? A cross-sectional SPECT-China study. Issue 8 (3rd August 2017) - Chen, Yi; Chen, Yingchao; Wang, Ningjian; Chen, Chi; Nie, Xiaomin; Li, Qin; Han, Bing; Xia, Fangzhen; Zhai, Hualing; Jiang, Boren; Shen, Zhoujun; Lu, Yingli
Abstract : Objective: Little is known about the association between thyroid nodules (TNs) and endogenous sex hormones. We aimed to investigate the relationship between TNs and sex-related hormones among men in China. Setting: The data were obtained from a cross-sectional study Survey on Prevalence in East China for Metabolic Diseases and Risk Factors (SPECT-China study, 2014–2015) based on the population. Participants: In total, 4024 men over 18 years of age who were not using hormone replacement therapy and who underwent complete assays of the serum total testosterone (T), oestradiol (E2 ), follicle-stimulating hormone (FSH), luteinising hormone (LH) and sex hormone-binding globulin (SHBG) levels as well as thyroid ultrasonography (US) enrolled in this study. Results: Of the 4024 participants (54.15±13.08 years old), 1667 participants (41.4%) had TNs. Men with TN(s) (TN(+) group) had significantly lower levels of total T and SHBG and higher E2 /T levels compared with the men without TN(s) (TN(−) group) (p<0.05). The TN prevalence decreased with the quartiles of the SHBG level (p<0.05). Binary logistic analysis showed that lower quartiles of SHBG had a greater risk of TN(s) (all p for trend <0.05). This association persisted in the fully adjusted model (p for trend=0.017), in which, for the lowest compared with the highest quartile of SHBG, the OR of TN(s) was 1.42 (95% CI 1.07 to 1.89). No statistically significant association was found between sex-related hormones and US characteristics associated with malignancy (nodule >10 mm, microcalcification and a 'taller' than 'wider' shape). Conclusions: TNs are highly prevalent in men in China. A lower SHBG level was significantly associated with TN among men. The potential role of SHBG in the pathogenesis of the TN remains to be elucidated.